2015
DOI: 10.1007/s00107-015-0894-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the cutting pattern and log provenance on size distribution of black spruce chips produced by a chipper-canter

Abstract: Chips of black spruce (Picea mariana (Mill.) B.S.P.) logs coming from two provenances, Montmorency (at 47°N) and Chibougamau (at 50°N) sites, were produced by a chipper-canter using three cutting widths (12.7, 19.1, and 25.4 mm). Chip dimensions were assessed by thickness, width, and length (Domtar and Williams classifications). Earlywood density, latewood density, ring density, ring width, rings per mm (R/mm), shear, splitting, modulus of elasticity (MOE), modulus of rupture (MOR) in bending, and basic densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 9 publications
3
15
0
Order By: Relevance
“…In kraft pulping, chemical penetration times vary in relation to chip size, thickness and uniformity. Uniform chips lead to more uniform pulping conditions and higher pulp recovery (Pulkki 1991;Broderick et al 1998;Ding et al 2005;True 2006;Färlin 2008;Inalbon et al 2011;Cáceres et al 2016a).…”
Section: Chip Quality and Chip Recovery Ratementioning
confidence: 96%
See 4 more Smart Citations
“…In kraft pulping, chemical penetration times vary in relation to chip size, thickness and uniformity. Uniform chips lead to more uniform pulping conditions and higher pulp recovery (Pulkki 1991;Broderick et al 1998;Ding et al 2005;True 2006;Färlin 2008;Inalbon et al 2011;Cáceres et al 2016a).…”
Section: Chip Quality and Chip Recovery Ratementioning
confidence: 96%
“…At higher MC the wood is softer and hence greater quantities of pins and fines will be produced (Watson and Stevenson 2007;Niedźwiecki 2011;Mihelič et al 2015;van der Merwe et al 2016a). No studies could be found to indicate optimal MC for chipping as wood processing is a function of the interactions between wood density and MC (Hernández and Lessard 1997;Niedźwiecki 2011;Spinelli and Magagnotti 2012;Cáceres et al 2015). Watson and Stevenson (2007) investigated the influence of seasonal variation in log MC of softwood and hardwood species on chip size and uniformity and the effect on kraft pulping.…”
Section: Chip Quality and Chip Recovery Ratementioning
confidence: 97%
See 3 more Smart Citations